Psicoterapia psicodramática com crianças: uma proposta socionômica - Filipini, Rosalba (2013)
This is a theoretical analysis of the fundamentals of Psychodrama with children. Being a conceptual work and focused on a specific form of psychodrama, literary production in this field was consulted and the practice in psychotherapy with children was analyzed. The goal was to discuss the structure and practice of psychodramatic psychotherapy with children, analyzing how the authors have been performing this type of work, in which aspects there is agreement and / or disagreement and the range, limits and specifics facing the proposed psychodramatic psychotherapy created by J. L. Moreno. The reflection on theory and infant clinical practice can contribute to the scientific, clinical and academic community, providing subsidies on professional practice. The analysis revealed that there is a division between psychodramatists working with children: those who seek other theoretical references and those who believe that the socionomics theory has a theoretical and practical framework underlying the psychotherapeutic work. There is unanimity in conceiving that preschoolers do not reverse roles: that the students need greater warming for dramatic action, as in psychotherapy with adults, as well as they benefit from psychodrama techniques.The technique of double-mirroring is an authors proposal, which is made possible when the counter-role played by the psychotherapist has symmetry with the role played by the child. Psychotherapy seeks the realization of a dramatic project that is co-built between child and psychotherapist. Sharing is understood as an existing and important stage in their psychotherapeutic process. Through discussion of the practice of psychodramatic psychotherapy with children, it was considered that the theory of spontaneity and creativity, sociometry, the role theory and the theory of the moment, offer subsidies to dramatic action and to the understanding of the process of child psychotherapy